DIGGING A DIVERSION CANAL TO PAINT THE PROBLEM OF FLOODING IN THE CITY OF NAKHON SI THAMMARAT AND CREATING INFORMATION TO COLLECT FOR STAKEHOLDERS - Phuttapruek, Wanpha; Chimhet, Pairet; Nunklam, Direk; Preecha, Nicharee; Wichakara, Phra Palad Thanwa (Journal of MCU Nakhondhat, 2023)
This research has the objectives of research consisting of 1) to study the conditions of the environment. and livelihoods of people in the community today, such as the household economy food security sociocultural life Wisdom for Lives Operate in accordance with current government guidelines 3) to study the potential of related communities in relieving flood problems in Nakhon Si Thammarat. and the conditions that create such potential Connecting to the proposed solutions of other sub-projects in the project series, and 4) to carry out the transfer of knowledge from items 1-3 to the public and relevant government agencies. as action research using interviews and focus groups. From a group of 175 key informants, including people in the affected area. and groups that play an important role in decision-making. used for descriptive content analysis The results of the research revealed that 1) the livelihood of people in the current community living according to the economic conditions that gradually change according to the development era 3) The potential of strong and united communities Unity and generosity have the potential to be self-reliant and learn to adapt to changes; 4) bringing knowledge from items 1-3 to the public and relevant government agencies found Guidelines for bringing knowledge discovered from research to the public and relevant agencies Driving information of villagers in upstream, midstream, and downstream areas.